How to contain artemisinin- and multidrug-resistant Falciparum malaria - Dondorp, A; Smithuis, F; Woodrow, C; von Seidlein, L (Cell Press, 2017)
In the Greater Mekong subregion (GMS), artemisinin resistance is increasingly compounded by partner drug resistance, causing high failure rates of artemisinin combination therapies in some areas. For its containment, an accelerated elimination strategy will be needed. This includes high-quality implementation of conventional malaria control measures: early case management with quality artemisinin combination therapies (avoiding artesunate monotherapies) and single gametocytocidal low dose of primaquine, vector control and surveillance. Village health workers (VHWs) play a key role in the provision of community-based services which have to reach even the most remote populations. Additional, more aggressive, approaches will be important to accelerate malaria elimination, which could include mass drug administrations, potentially in combination with ivermectin and vaccination, mass screening and treatment with novel diagnostics, reactive case detection, and other measures.